Komunikasi Organisasi Karang Taruna untuk Meningkatkan Motivasi Kreatif Anak Muda - Irwan Desyantoro; Rusmalia Dewi; Cristine Roselvia Tri Amelia (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Youth who have creative motivation, especially in Bangetayu Wetan Village, Semarang City, are a community forum for social welfare in the environment by being active in youth organization activities. To increase the knowledge and understanding of the importance of organizational communication to increase the motivation for creativity in the organization or the environment, training activities for members of the youth organization in Bangetayu Wetan Village. The method of lectures, games, discussions is the approach for the implementation of this community service activity. Based on the results of pretest and posttest data analysis using T-test, output results using SPSS tool are p < 0.01 where p (sig.) = 0.000 < 0.01. This can be interpreted that there is an increase in the understanding of the members of the youth organization regarding communication in a good and effective organization.